Reinforcement of aligned cellulose fibers by lignin-polyester copolymers. (December 2020) - Chee, P.L.; Yew, P.Y. Michelle; Kai, D.; Loh, X.J.
Abstract: With an ever-increasing attention on the climate change and the growing amount of plastic wastes generated, the search for an alternative to the petroleum-based plastics has never been as imperative. Inspired by the structure of natural wood, we aim to reproduce artificial equivalent using modified lignin and cellulose acetate. As natural wood are made up of an aggregation of fibers, electrospinning was used to produce the fiber component. Besides exploring the influence of various polymers on the properties of the eventual fibers, its properties were also examined in terms of its orientation – random and aligned. The addition of lignin copolymers was shown to remarkably improve the tensile strength and the Young's modulus of cellulose acetate fibers up to 500% and 7, 000% respectively. In contrast to the random fibers, the aligned fibers demonstrated better tensile strength and Young's modulus which could be attributed to the higher crystallinity. Among the fibers, the longitudinal aligned C.A. + Lig-PHB fibers exhibited the best tensile strength and Young's modulus which could be explored for load bearing applications. Graphical abstract: Image 1 Highlights: Various polymers were successfully grafted onto lignin via the solvent free ring opening polymerization. TBD appeared to be more suitable for the grafting of PTMC onto lignin than for PCL and PHB. Addition of grafted lignin improved the C.A. fibers mechanically and the best results was noted for the fibers with PHB. Longitudinally aligned fibers performed the best in terms of tensile strength and Young's modulus.